Insecticidal Potential of Matricaria chamomilla’s Essential Oil and Its Components (E)-β-Farnesene, Germacrene D, and α-Bisabolol Oxide A against Agricultural Pests, Malaria, and Zika Virus Vectors - Khalid A. Al-Ghanim; Kaliyamoorthy Krishnappa; Jeganathan Pandiyan; Marcello Nicoletti; Baskar Gurunathan; Marimuthu Govindarajan (Agriculture, 2023)
Agricultural and medical insect pests are damaging edible crops, spreading diseases, and harming non-target fauna and flora. Prominent polyphagous insect pests harass farmers in the agronomy sector, causing uncountable revenue corrosion. Ecofriendly phytopesticides can avoid the consequences of the bulk usage of synthetic chemicals. In this study, the toxic effect on third-instar larvae of four different insect species (Spodoptera litura, Helicoverpa armigera, Aedes vittatus, and Anopheles subpictus) and the bio-toxicity on non-target fauna (NTF) (Stegodyphus sarasinorum and Gambusia affinis) were evaluated using Matricaria chamomilla (Mc) essential oil (EO) and its major phytoconstituents (Mc-MPCs). GC–MS analysis of the studied M. chamomilla EO gathered 39 constituents, with (E)-β-Farnesene (24.3%), Germacrene D (9.4%), and α-Bisabolol oxide A (10.2%) accounting for the major constituents. Remarkable larval death was seen in H. armigera and Ae. vittatus. In addition, (E)-β-Farnesene, Germacrene D, and α-Bisabolol oxide A exhibited a relevant maximum toxic effect on the target pest’s third-instar larvae. The bio-toxicity of M. chamomilla EO and Mc-MPCs was tested on terrestrial and aquatic NTF. The LC50 values for S. sarasinorum and G. affinis ranged from 922.65 to 1750.49 µg/mL. M. chamomilla EO and its MPCs evidenced prospective phytopesticidal efficiency on selected agricultural and medical insect pests.